Longmire. The complete fourth season [videorecording (DVD)] - Taylor, Robert, 1963-; Sackhoff, Katee; Phillips, Lou Diamond, 1962-; Freeman, Cassidy, 1982-; Johnson, Craig, 1961- (Warner Bros., 2016)
The unflappable Sheriff Walt Longmire and his deputies are trying to put the troubling events of the past behind them. The mysterious White Warrior who tormented Branch is dead. Walt's best friend Henry Standing Bear is a free man. Longmire's right-hand deputy Victoria "Vic" Moretti is newly divorced. And the mystery of Walt's wife's murder is seemingly resolved. But, the opening of the new casino on the Reservation brings dark new problems to Walt's corner of Wyoming.